Cambodian Youth’s Perceptions About Code-Switching Between Khmer and English in Conversations: Insights from a Survey Study - Vitou Tes; Kimkong Heng (Scientia Publica Media, 2026)
Code-switching is the practice of alternating between two or more languages during communication, as speakers alternate between their native language and another language. This phenomenon usually happens to people with bilingual or multilingual competencies. In Cambodia, code-switching has become increasingly common, especially among young people who often use it in daily conversations. This study aims to examine Cambodian youth’s perspectives on code-switching between Khmer and English in daily conversations. The study collected data from Cambodian youth aged 18 to 35 using an online questionnaire distributed via Google Forms. Based on 261 responses from the respondents (48.7% were females), the study revealed common English words or phrases used in daily conversations. It also showed that most Cambodian youth (93.1%) experienced using code-switching in daily conversations. Almost two-thirds (60.9%) of them said that they sometimes used code-switching, while about 15% and 5% respectively stated that they often or always used it. The participants tended to disagree that code-switching between Khmer and English made them forget the Khmer language (M = 2.43, SD = 1.03). The main reasons for code-switching included using it to practice English, express and elaborate details, show bilingual competency, and deal with a lack of vocabulary. The study also showed a positive correlation between the English proficiency level and the frequency of code-switching use (r = 0.257, p < 0.01). This means that those who are more proficient in English tend to engage in code-switching more often in everyday conversations. This study concludes by discussing limitations and suggestions for future research.